Food Security and Climate Change in the Asia-Pacific Region: Evaluating Mismatch between Crop Development and Water Availability - Huda, Samsul; Sadras, Victor; Wani, Suhas; Mei, Xurong (International Journal of Bio-resource and Stress Management, 2023)
Phenological development is the single most important attribute of crop adaptation to shifting climates. Climate change may alter the rate of phenological development and the amount and distribution of rainfall during the growing season. These changes may in turn result in mismatch between water demand by crops and water availability from rainfall. This paper illustrates how an understanding of the impact of climate shifts on key crops will enable the Asia-Pacific farmers, community workers and policy agencies to better prepare and adapt to climate change. Strategies include changes to existing policy and practices, for example, timing of planting, managing rainwater resources, use of new varieties, disease management protocols, alternate crops and shift in geographic distribution of crops. An international project is described which combines a new analysis of realized changes in meteorological parameters, and use of estimates from published work on future climates to assess temporal shifts in crop phenology, likely shifts in the pattern of rain and water availability, mismatch between crop phenology and water availability, and the expected consequences of this mismatch for food security.